2000
DOI: 10.1097/00000658-200006000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy in the Community Hospital in Patients Age 80 and Older

Abstract: ObjectiveTo determine whether the rates of death and complications of carotid endarterectomy (CE) were different in the octogenarian population than in patients younger than age 80. Summary Background DataThe utility of CE depends on the ability of the surgeon and hospital to attain low rates of death and complications, including all subgroups of the patient population. In the past 30 years, the number of people age 85 and older has increased 274%. MethodsDetailed chart review was carried out on all CE procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…The perioperative mortality rate in our octogenarian sample (2.2%) is consistent with other studies that report 30-day mortality rates between 0 and 3.6% [14,15,16,18,19,20,21,22,23,24,25,27,28,29,31,32,39,40]. Most of these studies were of modest sample size [14,15,16,18,19,20,21,22,23,24,25,27,28,29,32], included patients from single medical centers or states [15,16,20,22,23,24,25,26,27,32], or described outcomes within a single surgical practice [18,19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The perioperative mortality rate in our octogenarian sample (2.2%) is consistent with other studies that report 30-day mortality rates between 0 and 3.6% [14,15,16,18,19,20,21,22,23,24,25,27,28,29,31,32,39,40]. Most of these studies were of modest sample size [14,15,16,18,19,20,21,22,23,24,25,27,28,29,32], included patients from single medical centers or states [15,16,20,22,23,24,25,26,27,32], or described outcomes within a single surgical practice [18,19].…”
Section: Discussionsupporting
confidence: 92%
“…Most of these studies were of modest sample size [14,15,16,18,19,20,21,22,23,24,25,27,28,29,32], included patients from single medical centers or states [15,16,20,22,23,24,25,26,27,32], or described outcomes within a single surgical practice [18,19]. Only a few studies reported rates for nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 7 papers reported risks in older patients but did not compare their results to younger patients in the same centre(s) and were therefore excluded. Among the 62 remaining eligible papers [35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97], there were no differences in the associations between either age or sex and overall 30-day stroke rate, death rate or combined stroke and death rate between studies reporting the associations as their primary aim and those which reported them as a subanalysis along with other risk factors (fig. 1, 2) and so data from both types of study are combined in the analyses below.…”
Section: Resultsmentioning
confidence: 99%
“…3 From observational studies, the periprocedural risk for the elderly undergoing CEA has been reported to be comparable to the risk for younger patients. [3][4][5] Nevertheless, subgroup analyses for age in several randomized trials revealed that periprocedural risk of stroke, myocardial infarction, and death after carotid artery stenting (CAS) increases with age. 6 -9 The occurrence of periprocedural stroke for CAS has been proposed to be closely related to plaque manipulation with intra-arterial devices resulting in plaque rupture, subsequent superimposed thrombus formation, and embolization of plaque debris.…”
mentioning
confidence: 99%